Effects of wetland, tide, and season on benthic biofilms and related sediment properties in mangrove ecosystems - Yang, Lihua; Yang, Qian; Lin, Li; Luan, Tiangang; Yang, Qiong; Li, Pu; Tam, Nora F. Y. (Frontiers in Marine Science, 2022)
Sediment biofilms, mainly composed of diatoms, bacteria and related extracellular polymeric substances (EPS), play important roles in mangrove ecosystems. In order to better understand the microbial biodiversity in marine environment, based on the in situ investigation in two mangrove wetlands in Pearl River Estuary in South China, this study clarified the effects of wetland, season and tide on sediment biofilms and related sediment properties. Owing to the tide current, the northeastern Futian is more influenced by seawater than the southwestern Qi’ao. As a consequent of the salinity-driven accumulation of nutrients in sediments, Futian was more eutrophic than Qi’ao. Compared to Qi’ao, higher nutrimental condition in Futian conserved higher abundance of eutrophic indicators of Nitzschia and Cyclotella, which results in higher values of all pigments and bound-polysaccharide with varied monosaccharide composition. Compared to the seaward site, the landward site has higher abundance of benthic (pennate) diatoms but lower abundance of planktonic (centric) diatoms due to the varied settling velocity by tidal disturbance. This varied diatom composition led to higher levels of bound-polysaccharide and most monosaccharides in the landward site than seaward site. Compared to late spring (March), early summer (May) appears similar diatom abundance but more EPS fractions (except bound-protein) and most monosaccharides due to the higher light intensity and temperature. However, the observed lower bacterial abundance in May than March might be due to the higher predation pressure. The baseline data on biofilm compositions in mangrove ecosystems from this study can improve the understanding of the microbial carbon loop driven by benthic biofilms.